Intermittent Water Supply Impacts on Distribution System Biofilms and Water Quality - Calero Preciado, Carolina; Husband, Stewart; Boxall, Joby; del Olmo, Gonzalo; Soria-Carrasco, Víctor; Maeng, Sung Kyu; Douterelo, Isabel (Water research (Oxford), 2021)
•Short times of IWS have a higher risk of DBPs formation.•Long times of IWS supply led to a high risk of discolouration events.•IWS events changed biofilm and planktonic microbial communities of DWDS.•Long IWS times favor the risk associated to potential pathogenic microorganisms. Intermittent water supplies (IWS) are routinely experienced by drinking water distribution systems around the world, either due to ongoing operational practices or due to one off interruptions. During IWS events changing conditions may impact the endemic biofilms leading to hydraulic mobilisation of organic and inorganic materials attached to pipes walls with a resulting degradation in water quality. To study the impact of IWS on the microbiological and physico-chemical characteristics of drinking water, an experimental full-scale chlorinated pipe facility was operated over 60 days under realistic hydraulic conditions to allow for biofilm growth and to investigate flow resumption behaviour post-IWS events of 6, 48 and 144 hours. Turbidity and metal concentrations showed significant responses to flow restarting, indicating biofilm changes, with events greater than 6 hours generating more turbidity responses and hence discolouration risk. The increase in pressure when the system was restarted showed a substantial increase in total cell counts, while the subsequent increases in flow led to elevated turbidity and metals concentrations. SUVA254 monitoring indicated that shorter times of non-water supply increased the risk of aromatic organic compounds and hence risk of disinfection-by-products formation. DNA sequencing indicated that increasing IWS times resulted in increased relative abundance of potential pathogenic microorganisms, such as Mycobacterium, Sphingomonas, and the fungi Penicillium and Cladosporium. Overall findings indicate that shorter IWS result in a higher proportion of aromatic organic compounds, which can potentially react with chlorine and increase risk of disinfection-by-products formation. However, by minimising IWS times, biofilm-associated impacts can be reduced, yet these are complex ecosystems and much remains to be understood about how microbial interactions can be managed to best ensure continued water safe supply. [Display omitted]